1990
DOI: 10.1161/01.cir.82.4.1289
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation of refractoriness within a reentrant circuit during ventricular tachycardia. Relation to termination.

Abstract: Programmed ventricular stimuli introduced during sustained monomorphic ventricular tachycardia frequently reset the tachycardia, resulting in a less than fully compensatory pause. A resetting response curve is generated when the set of return cycles is evaluated as the function of the coupling intervals of the extrastimuli delivered during the ventricular tachycardia. If

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…[32][33][34][35] In a study by Almendral et al 36 in 32 patients with chronic myocardial infarction, the 3 different reset patterns were approximately equally distributed. In another clinical study, Gottlieb et al 37 found that termination of VT by premature stimuli was more likely if the reentrant VT exhibited a sloped reset curve. VT cycle length did not determine the type of response during reset of the tachycardia.…”
Section: Differential Effects Of a Segment Of Slow Conduction On Resementioning
confidence: 98%
“…[32][33][34][35] In a study by Almendral et al 36 in 32 patients with chronic myocardial infarction, the 3 different reset patterns were approximately equally distributed. In another clinical study, Gottlieb et al 37 found that termination of VT by premature stimuli was more likely if the reentrant VT exhibited a sloped reset curve. VT cycle length did not determine the type of response during reset of the tachycardia.…”
Section: Differential Effects Of a Segment Of Slow Conduction On Resementioning
confidence: 98%
“…[1][2][3][4][5][6] Flat portions were short, unlike in clinical responses where flat portions occur over as much as 50% of the cycle. 1 This difference may be related to different substrates forming reentrant circuits (discussed below).…”
Section: Resetting Response Curves Of Canine Ventricular Tachycardiamentioning
confidence: 99%
“…Different resetting responses may be elicited clinically from different sites of stimulation, and termination of clinical ventricular tachycardia in response to premature simulation is dependent in part on the steepness of the response. 5 Boersma et al 11 were unable to demonstrate resetting in a rabbit model of anisotropic reentry and concluded that "it seems very unlikely that clinical tachycardia based on functional reentry can be reset." This disparity with our results reflects differences in the models of reentry that may have important clinical implications for understanding human ventricular tachycardia.…”
Section: Activation Maps and Resetting Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…T HE conductive properties of the atrioventricular (AV) node and the accessory pathway are relatively well known,1)-4) and dual pathways have been demonstrated as the cause of reentry in the AV node.4)- 6) In ventricular tachycardia (VT), resetting by a single extrastimulus7), 8) or transient entrainment9),10) might be used to disclose the conductive characteristic of the slow conduction zone, but data concerning the electrophysiologic properties of reentry circuits in human ventricular tachycardia have been recently accumulating.…”
mentioning
confidence: 99%